Synthesis, spectral characterization, electron microscopic study and thermogravimetric analysis of a phosphorus containing dendrimer with diphenylsilanediol as core unit - Dadapeer, E.; Babu, B. Hari; Suresh Reddy, C.; Charmarthi, Naga Raju (Beilstein Journal of Organic Chemistry, 2010)
A phosphorus containing dendrimer with a diphenylsilanediol core was synthesized using a divergent method. Several types of reactions were performed on dendrons of several sizes, either at the level of the core or the surface. The giant Schiff’s base macro molecule possesses 12 imine bonds and 8 hydroxy groups on the terminal phenyl groups. The structures of the intermediate compounds were confirmed by IR, GCMS and 31P NMR. The final compound was characterized by 1H, 13C, 31P NMR, MALDI-TOF MS and CHN analysis. Scanning electron microscopic and thermogravimetric analysis/differential scanning calorimetric studies were also performed on the final dendritic molecule.
Keywords: diphenyl silanediol; divergent method; phosphorus containing dendrimer; scanning electron microscopy; Schiff’s base; thermogravimetric analysis